A highly miniaturized freestanding kinetic-impact-based non-resonant hybridized electromagnetic-triboelectric nanogenerator for human induced vibrations harvesting. (1st December 2020) - Toyabur Rahman, M.; Sohel Rana, SM; Salauddin, Md.; Maharjan, Pukar; Bhatta, Trilochan; Kim, Hyunsik; Cho, Hyunok; Park, Jae Yeong
Graphical abstract: Highlights: A miniaturized hybridized nanogenerator for harvesting human-induced vibrations. Non-resonant system with nonlinearity for high outputs at low-frequency vibrations. Nanowire and micro-nano hierarchical structured TENG for increasing performance. A customized power management circuit for practical use of hybridized nanogenerator. Demonstration of the harvester as a portable power source for modern electronics. Abstract: Energy harvesting from human motion can be considered a promising and sustainable energy source for powering portable electronics and sensors. Herein, a highly miniaturized freestanding kinetic-impact-based hybridized nanogenerator (MFKI-HNG) is presented to harvest human-induced vibrations effectively. The MFKI-HNG was designed to simultaneously generate hybridized outputs under the same mechanical load through a rational integration of an electromagnetic generator (EMG) and a freestanding-mode triboelectric nanogenerator (TENG). A non-resonant mechanical system with nonlinearity significantly improved the EMG's output performance in the low-frequency vibration range (≤5 Hz). Subsequently, nanowire and micro-nano hierarchical structures developed on tribo-materials further enhanced the output performance of the TENG. After optimizing via theoretical modeling and simulations, the as-fabricated MFKI-HNG was tested using both shaker and human motions. The MFKI-HNG generated maximum output powers of 102.29 mW across the optimum resistances, with a corresponding normalized power density of 3.67 mW cm −3  g −2 at 5 Hz under 10 ms −2 (1 g = 9.8 ms −2 ). During diverse activities, the MFKI-HNG could harvest a significant amount of energy in different body-worn positions and drive thermo-hygrometers and 380 commercial light-emitting diodes simultaneously. Using a customized power management circuit, the MFKI-HNG can act as a portable power source for modern electronics, such as smartphones and smartwatches. A wireless temperature sensor has successfully run continuously for more than 70 s with the MFKI-HNG from just 6 s of excitations. This study shows the immense potential of harvesting human-induced vibrations via a hybridized nanogenerator for developing a feasible self-powered system for portable/wearable electronics and wireless healthcare monitoring systems.